Mineral Stabilization Slows Losses of Peatland Carbon Following Long‐Term Drainage for Agriculture - Katy J. Faulkner; Katerina Georgiou; David A. Coomes; Philippa Ascough; Anna Basford; Rodney G. O. Burton; Romy Copley; Emma Keerberg; Alanie Lapina; Kimber Moreland; Christopher Evans; Ross Morrison; et al. (Global Change Biology, 2026)
Cultivated peatlands are a major CO 2 emission source, but the processes that regulate the decomposition of drained peat are debated, especially as drained peat becomes increasingly shallow. Many cultivated peatlands are underlain by a mineral soil layer. Surface subsidence, oxidation and tillage reduce the peat thickness, which intermixes peat with minerals as peat is lost. A key question is whether this mixing can reduce emissions by making soil organic carbon (SOC) more stable by transforming particulate organic carbon (POC)—which dominates the carbon stock in deep drained peatlands and is readily accessible to microbial decomposers—into mineral‐associated organic carbon (MAOC), which is less accessible to decomposers. To explore this question, we surveyed ten sites across the East Anglian Fens in England, a once extensive (~3900 km 2 ) peatland landscape that has been drained for cultivation since the mid‐seventeenth century. We used variation in cultivation to establish a peat loss gradient to evaluate how topsoil SOC (0–40 cm) and its forms change as peat is lost. As the peat was lost, the soils became rich in minerals (rising from 46% to 88% silt+clay content), resulting in an initial 11‐fold rise in newly‐formed MAOC, but a monotonic decline and near‐total loss of POC. POC turnover times were 3158 ± 62 years, indicative of peat, and POC was always older than MAOC; consequently, microbially‐processed peat along with gradual contributions of recently fixed carbon were sources of MAOC. A four‐month laboratory incubation showed that the MAOC:POC ratio was negatively correlated with respiration. We conclude that long‐term carbon retention via MAOC formation has the potential to reduce carbon loss from degraded, mineral‐mixed peatlands. However, because this MAOC pool is itself vulnerable to loss under continued agricultural drainage, this mechanism is expected to slow rather than halt long‐term soil carbon loss from drained peatlands.